2009
DOI: 10.1590/s1516-35982009000900016
|View full text |Cite
|
Sign up to set email alerts
|

Fontes e níveis de metionina em dietas para frangos de corte

Abstract: Objetivou-se avaliar o efeito de duas fontes de metionina, DL-metionina e metionina hidroxi análoga (MHA-AL), e de três níveis de suplementação desse aminoácido em dietas comerciais sobre o desempenho de frangos de corte. Foram utilizados 1.232 pintos de corte machos da linhagem Ross, de 1 a 47 dias de idade, distribuídos em delineamento inteiramente casualizado, em esquema fatorial 2 X 3 (fonte de metionina X nível de suplementação) e uma dieta adicional (basal) sem suplementação, com oito repetições de 22 av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
4
1
Order By: Relevance
“…This result shows that there was 15.29 and 9.73% improvement in gain and 8.43 and 6.27% in feed conversion, respectively, for both DLM-65 and DL-HMB. These results differed from those previously reported by Payne et al (2006) and Viana et al (2009), who observed similar performance responses in birds that were supplemented with increasing levels of DL-HMB or DLM in an amount equivalent to 65% according to the amount of each level of DL-HMB.…”
Section: Resultscontrasting
confidence: 99%
“…This result shows that there was 15.29 and 9.73% improvement in gain and 8.43 and 6.27% in feed conversion, respectively, for both DLM-65 and DL-HMB. These results differed from those previously reported by Payne et al (2006) and Viana et al (2009), who observed similar performance responses in birds that were supplemented with increasing levels of DL-HMB or DLM in an amount equivalent to 65% according to the amount of each level of DL-HMB.…”
Section: Resultscontrasting
confidence: 99%
“…Other studies, including Buresh and Harms (1986), Schutte and Weerden (1987) and Costa and Bastiani (1997), also found no significant differences in feed intake when comparing two methionine sources (DLM-99% and HMTBA-88%). Meanwhile, Viana et al (2009) studied two dietary methionine sources (DLM-99% and HMTBA-88%) observed no significant difference in feed intake.…”
Section: Resultsmentioning
confidence: 93%
“…() and Viana et al. () observed equivalence between supplemental methionine sources and the DLM‐99% (standard) source when studying supplemental methionine sources in the diet of broilers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations